Quantificação de vitamina a em concentrados polivitaminicos por cromatografia líquida de alta eficiência - Giacomini, Leandro Zanini (2006)
Nowadays the importance and interest for vitamins in human and animal health increased. When vitamin concentration is low in the raw material and is necessary to add multivitamin complexes to the animal diet a representative cost is incorporated to animals nutrition. The proposal of this study was evaluation and validation of a methodology by high performance liquid chromatography to quantify vitamin A in polyvitamin concentrates for animal nutrition. The method developed was adapted for the Micotoxicologic Analysis Laboratory conditions, placed at Universidade Federal de Santa Maria (RS), from a method published at United States Pharmacopoeia . The vitamin A extraction from concentrates was done using hexane as extraction solvent after hydrolysis and saponification. The recovery found for this method was 85.98% with a mean of relative standard deviation (RSD) of 1,52% at the repetition test using premix samples. All analyses were performed using a HPLC system with UV detection at 325 nm, a reversed phase column at 1 mL/min flow rate and 40oC of temperature. The mobile phase used was methanol:water (98:2, v/v) at isocratic mode. The calibration curve was constructed using standard vitamin A (All-trans-retinol) at concentrations varying from 0.475 to 9.50 μg/mL. The correlation coefficient (r2) was 0.9995, the detection limit 0.095 μg/mL and quantification limit of 0.24 μg/mL for Aderex (compound without vitamin A with non uniform particles) fortified samples.Observing the results obtained, in 15 premix samples analyzed, six samples (40 %) of them present values of vitamin A greater than the desired concentration. Four samples (26,67 %) had values bellow the expected and only five (33,33 %) presented values between the minimum and maximum preconized for birds and pig nutrition. In this way, this method was efficient, rapid and precise for routine analysis providing in this way, an important instrument for quality control in animal nutrition area.